Community Green Map of Victoria and Region: a guide to our city, land, people and food ... - Common Ground Community Mapping Project (University of Victoria Libraries, 2021)
A map showing sites of ecological and social value in and around Victoria, BC, as identified through community input and discussion. Icons from the international Green Map System are used to identify each site. First Nations illustrations by Songees artist Butch Dick, and cartography by Ken Josephson. Reverse of map features sections about the process of making the map, the Green Map System, and information on International Community Mapping; facts about Victoria; community mapping initiatives; contributions from children and youth mapping; and a list of regional resources, web sites and other initiatives. Many community members contributed to this project, a number of them, along with sponsors and other contributors are named on the map itself. This map is part of the Green Map System. ...